Optimized configuration of a hose reel traveling irrigator - Ge, Maosheng; Wu, Pute; Zhu, Delan; Zhang, Lin; Cai, Yaohui (Agricultural water management, 2020)
•Guidance is provided on a method to optimize a hose reel traveling irrigator.•Two technical, two economic, and three social and environmental factors were evaluated.•The results of two statistical methods agree.•Optimization with and without social and environmental factors bring inconsistent results. This study aims to identify the optimal configuration of a hose reel traveling irrigator based on a multi-objective evaluation. We identified nine evaluation indicators (two empirical: irrigation efficiency, yield increase; two technical: spray uniformity, application rate; two economic: initial investment, annual operating costs; three social and environmental: labor intensity, productivity, greenhouse gas emissions) selected from aspects of technology, economy, society and the environment. We evaluated a primary set of seven technical, economic, and social and environmental indicators and a smaller subset of only the technical and economic indicators. The multi-objective evaluation ranked 144 alternatives using Principal component analysis and Data envelopment analysis methods. The optimal scheme was exactly the same for both analysis methods, and the number of schemes within a deviation of five reached 88.2 % of all alternatives. The comparison results support the accuracy of the evaluation and the results were not affected by the evaluation methods. The influence of a single configuration parameter on the comprehensive evaluation efficiency of the hose reel traveling irrigator was discussed. A 200 m pipe length, 0.45 MPa operating pressure of the sprinkler, 0.2R overlapping distance and 65 mm pipe diameter was preferred under the working conditions of the case study. The impacts of social and environmental indicators on the overall evaluation were significant, which can help designers/users make cleaner and more user-friendly configuration schemes of the hose reel traveling irrigator.